2017
DOI: 10.1310/sci2304-299
|View full text |Cite
|
Sign up to set email alerts
|

Important Clinical Rehabilitation Principles Unique to People with Non-traumatic Spinal Cord Dysfunction

Abstract: Non-traumatic spinal cord dysfunction (SCDys) is caused by a large range of heterogeneous etiologies. Although most aspects of rehabilitation for traumatic spinal cord injury and SCDys are the same, people with SCDys have some unique rehabilitation issues. This article presents an overview of important clinical rehabilitation principles unique to SCDys. Electronic literature search conducted (January 2017) using MEDLINE and Embase (1990-2016) databases for publications regarding SCDys. The focus of the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 76 publications
(139 reference statements)
0
31
1
Order By: Relevance
“…The study has some limitations that need to be addressed: the number of patients in this study was rather small, despite we used the data of the largest European database. This reflects the relative small number of patients with ischemic SCI admitted to specialized SCI centers . The low number of subjects resulted in broad confidence intervals of the aROCs and in the impossibility of exploring the effects of differences in the clinical composition of the traumatic and ischemic patient groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study has some limitations that need to be addressed: the number of patients in this study was rather small, despite we used the data of the largest European database. This reflects the relative small number of patients with ischemic SCI admitted to specialized SCI centers . The low number of subjects resulted in broad confidence intervals of the aROCs and in the impossibility of exploring the effects of differences in the clinical composition of the traumatic and ischemic patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…This reflects the relative small number of patients with ischemic SCI admitted to specialized SCI centers. 24 The low number of subjects resulted in broad confidence intervals of the aROCs and in the impossibility of exploring the effects of differences in the clinical composition of the traumatic and ischemic patient groups. However, based on the validity of the model in the population of traumatic SCIs and on the representativeness of our sample of the entire ischemic population, we believe that the results presented here may be seen as sufficiently relevant to justify application in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare systems and NTSCI management models must consider the differential prognoses and mortality outcomes identified between NTSCI etiological groups to aid in the development of specialized inpatient and outpatient rehabilitation programs. For example, individuals with progressive forms of NTSCI (e.g., malignant and benign tumors) can benefit from short-term rehabilitation plans, with optimized goals, aimed at improving vital aspects of functioning (e.g., bladder management and caretaker education) [28][29][30]. Individuals with an infection and cardiovascular etiology additionally require intensive routine checks and up-to-date vaccinations to minimize medical complications that can interfere with rehabilitation [31].…”
Section: Personalized Rehabilitation and Long-term Follow-up Programsmentioning
confidence: 99%
“…Individuals with an infection and cardiovascular etiology additionally require intensive routine checks and up-to-date vaccinations to minimize medical complications that can interfere with rehabilitation [31]. Specialized outpatient follow-up care can play a vital role for the prevention and treatment of complications secondary to NTSCI [29]. Outpatient services, such as the Swiss-based ParaHelp [32], can provide individuals with NTSCI with quality advice and counseling and reduce patient burden associated with…”
Section: Personalized Rehabilitation and Long-term Follow-up Programsmentioning
confidence: 99%
“…This applies especially if the desire is to include only one specific cause of SCDys, which is appropriate in some studies because of the differences in outcomes reported between the etiologies. 43,47 The acute hospital management of SCDys and rehabilitation services for these people tend to be decentralized; most people with SCDys are not admitted to specialist spinal cord units in acute or rehabilitation hospitals. 28,29,31,48,49 This creates significant challenges when planning multicenter studies (such as internal and external funding or resource planning and performance monitoring) and makes a population-based registry for these patients extremely difficult.…”
Section: Identification Of Casesmentioning
confidence: 99%